Multi-Cellular Functions of MG53 in Muscle Calcium Signaling and Regeneration - Benissan-Messan, Dathe Z.; Zhu, Hua; Zhong, Weina; Tan, Tao; Ma, Jianjie; Lee, Peter H. U. (Frontiers in Physiology, 2020)
Since its identification in 2005, multiple studies have indicated the importance of MG53 in muscle physiology. The protein is produced in striated muscles but has physiologic implications reaching beyond the confines of striated muscle. Roles in muscle regeneration, calcium homeostasis, excitation-contraction coupling, myogenesis, and the mitochondria highlight the protein’s wide-reaching impact. Numerous therapeutic applications could potentially emerge from these physiologic roles. This review summarizes the current literature regarding the role of MG53 in skeletal muscle. Therapeutic applications are highlighted.